The effectiveness of olmesartan on inflammation at cardiopulmonary bypass - Özgüler, İbrahim Murat; Üstünel, Latif (My University, 2021)
Aim: Systemic inflammatory response syndrome may develop after coronary artery bypass graft surgery that performed by cardiopulmonary bypass technique. It is known that olmesartan, an angiotensin II receptor blocker, has anti-inflammatory effects. The antiinflammatory efficacy of olmesartan treatment was investigated in patients undergoing cardiopulmonary bypass.Materials and Methods: The study included 50 patients (14 female, 36 male) between 30-80 years of age were underwent CABG surgery. Patients were randomly assigned to control (Group C) and olmesartan (Group O) gruoups. Group O were treated with a single dose of 10 mg per day; 5 days preoperatively and 35 days postoperatively, 30 mg at the operation day. Samples were taken before the induction of anesthesia (T1), 5 minutes before cross clamping (T2), 5 minutes after cross clamping (T3), after protamine infusion (T4), postoperative day 3 (T5) and postoperative day 35 (T6) for total serum levels of IL-6, IL-10 and IL-18; for h-CRP levels preoperative (T1) and postoperative day 35 (T2).Results: Statistically significant decrease of CRP levels were observed on the postoperative 35th day in Group O (p<0.05). Statistically significant decrease of IL-6 levels were observed in the Group O after protamine infusion (T4) and postoperative 3rd day (T5) (p <0.05).There was a statistically significant increase at 5 min. after the cross declamping time (T3) for IL-10 levels (p<0.05).Conclusion: Although the anti-inflammatory efficacy of olmesartan has been proven, it can be accomplished by combining it with drugs that have anti-inflammatory effects like statins or dose increasing.
Keywords: Genel ve Dahili Tıp; Kalp ve Kalp Damar Sistemi